PEMBELAJARAN MATEMATIKA TENTANG PENGUKURAN WAKTU, PANJANG DAN BERAT DI SEKOLAH DASAR - Unaenah, Een; Rafidah, Aura Rahmatun; Tsabitah, Jihan Fitri; Septia, Nirmala (Transpublika Publisher, 2023)
The purpose of this research is to describe how well the students at SDN Cipondoh 02 which is located on Jl. KH Hasyim Ashari, RT.002/RW.01, Nerogtog, Kec. Pinang, Kota Tangerang, Banten 15148, understands the material for measuring time, length and weight. This study looked at how well students understood the material for measuring length, time, and weight. This survey was conducted on 25 students, which was also conducted through interviews with the homeroom teacher of class IV students at SDN Cipondoh 02. Many students already understand measurement, but there are students who still don't understand it, according to the results of interviews and studies that have been conducted. The methods used to obtain this information are interviews, observation, and asking questions (tests). After getting the results, the data is then examined using qualitative data analysis techniques. Based on interviews, observations, and asking questions (tests), 75% of students already know the content of the measurement, and 25% of students still have difficulty understanding it. This is caused by various circumstances that affect students.